2019
DOI: 10.1002/mawe.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Improved tensile properties of basalt fibre reinforced polymer composites using silica nanoparticles

Abstract: In this study, the effect of silica nanoparticles as the reinforcing filler on the tensile response of basalt fibre reinforced polymer (BFRP) composite was investigated. A 40 wt.% nanosilica gel in epoxy was used to prepare a series of nanocomposites with 5 wt.%, 15 wt.% and 25 wt.% nanosilica. Static uniaxial tensile tests were conducted on the basalt fibre reinforced polymer composite to investigate the stress‐strain response of the unmodified and nanomodified composites. It was found that the incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…The addition of nanosilica in FRP composites was also extensively studied by Jumahat and coworkers [ 2 , 16 , 17 , 18 , 19 , 20 ]. It was found that the addition of nanosilica significantly improved the mechanical properties of the carbon fiber reinforced polymer (CFRP).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of nanosilica in FRP composites was also extensively studied by Jumahat and coworkers [ 2 , 16 , 17 , 18 , 19 , 20 ]. It was found that the addition of nanosilica significantly improved the mechanical properties of the carbon fiber reinforced polymer (CFRP).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the presence of spherical silica nanoparticles stiffened the epoxy matrix and offered better lateral support to the carbon fiber, thus improving the compressive properties [ 18 ]. In another study, the presence of nanosilica increased tensile strength up to 60% and improved ductility and toughness of basalt fiber reinforced composites [ 20 ]. The incorporation of silica nanoparticles was also found to improve the open hole compressive strength and stiffness of glass fiber reinforced polymer (GFRP), Kevlar fiber reinforced polymer (KFRP) and hybrid GFRP/KFRP composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of possible replacement is basalt fibre. Mineral natural fibres are not new, but their suitability as reinforcement in polymer composite is relatively new issue [ 3 , 4 ]. Basalt fibre is an inorganic fibre that has good strength, modulus, better strain to failure than carbon fibre, high operating temperature range, good chemical resistance, excellent heat and sound insulation properties, low water absorption, easily processed, eco-friendly and inexpensive [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties enable basalt fibre to be applied in geopolymeric concrete, pressure pipes, fibrous insulators, protective clothes, naval applications and fire-blocking materials [ 7 , 8 ]. Over the years, Basalt fibres have been hybridized with traditional fibres such as carbon fibre and glass fibre to develop structural materials [ 4 , 5 , 9 ], and also considered as replacement to traditional fibres by comparing their mechanical properties [ 3 , 7 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%